Faktor – Faktor Yang berhubungan dengan Kejadian Premenstrual Syndrome (PMS) pada Mahasiswi - Almujahidiani, Titik; Mayasari, Rini (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2023)
WHO premenstrual syndrome (PMS) has a higher prevalence in Asian countries compared to Western countries. According to the World Health Organization (WHO) there are more than half of the world's population under the age of 25 and 80% of them live in developing countries. The prevalence of premenstrual syndrome sufferers in the world according to Fatimah's research (2019) in Lebanon is 54.6% and in Sri Lanka it is 65.7%. Then the prevalence of premenstrual syndrome in Iran is 98.2%, in Brazil it is 39%, in Australia it is 44% and in Japan it is 34% (Alvionita, 2019). The method used in this research is an analytic survey with a cross sectional approach. The statistical test used is the chi-square test and logistic regression. The population of this study were all female students at levels I-III of the DIII Midwifery Study Program at the Budi Mulia Sriwijaya STIKes in 2023 with a total population of 112 female students, that is, all the total population. The analysis used was univariate, bivariate and multivariate analysis. Univariate analysis showed that 63 respondents (56.3%) had early menarche, 49 respondents (43.8%) had low knowledge, 55 respondents (49.1%) had abnormal nutritional status. The test results showed that there was no significant relationship between the age of menarche and the incidence of premenstrual syndrome (PMS) p.value 0.760, for knowledge with the incidence of premenstrual syndrome (PMS) p.value = 0.760, there was a relationship between nutritional status and the incidence of premenstrual syndrome (PMS) ) p. value = 0.012. The most dominant variable is nutritional status with an Exp (B) value of 2.972. The results of this study are expected to be able to add to students' insights about the importance of maintaining reproductive health.